Perception of graduates on the relevance of their academic training in the work environment - Quintana Carrascal, Yener Fabian; Luna Quintero , Juan Carlos; Ballesteros Torres , Yineth Paola; Trigos Duarte, Edgar Fernando (Universidad Francisco de Paula Santander, 2025)
The alignment of university education with the needs of the labor market is essential for the professional success of graduates. The objective of this research is to analyze the perception of UNAD-Ocaña graduates regarding the relevance of their academic training for job performance. Method. Quantitative cross-sectional descriptive research, using a questionnaire on a Likert-type scale where the variables are analyzed: relevance of the curriculum, satisfaction with the program, impact on society and image of the graduate. Results.  In the analysis of descriptive measures, the highest average was obtained in the variable image of the graduate 4.8, which reinforces the positive reputation of the University. Following this result with an arithmetic mean of 4.7 is the variable impact on society. The relevance of the academic curriculum is directly related to the ability of graduates to face the demands of the labor market, a variable in which an arithmetic mean of 4.6 was obtained and in the variable satisfaction of the program, which is closely linked to professional success and the evaluation. of the career in the work environment an average of 4.0 was obtained.  Discussions and conclusions. The positive results obtained in UNAD-Ocaña graduates related to the relevance of the curriculum, the satisfaction of the program, the impact on society and the image of the graduate reflecting the effectiveness of the programs offered by developing competencies that prepare the students to successfully face the labor market and contribute significantly to society.